Optimization of Microplate Type Uv-vis Spectrophotometer Performance as an Antioxidant Activity Testing Instrument - F. Widhi Mahatmanti; Nuril Huda; Ridho Prasetyo; Martin Sulistyani (Indonesian Journal of Chemical Science, 2024)
Eliminating a compound's capacity to impede and neutralize free radical-induced oxidation processes is the goal of antioxidant activity analysis. The DPPH (pikrilhidrazil-2,2-difenil-1) method was the approach taken in this investigation. Simple, sensitive, stable, quick, straightforward, and suitable for usage with tiny sample volumes are some of the benefits of DPPH procedures. In this investigation, some plant extracts were employed as a comparison, with ascorbic acid serving as the control. In order to evaluate a microplate-type uv-vis  Spectrophotometer effectiveness as an antioxidant activity test tool, the study will determine its maximum wave, linearity, accuracy, and IC50 values. Wavelength selectivity is found in 517 nm. The results validation of the DPPH method for analyzing the activity of antioxidants. Measurements of the ascorbic acid solution as a control obtained R2 values of 0.9781 compared to the LoD and LoQ limits of 0.961 and 3.053 respectively. The IC50 of ascorbic acid, ginger and turmeric, respectively, was 14.7218 (strong), 29.9194 (very strong), and 52.4943 (strong).